Practicing Other-Focused Kindness and Self-Focused Kindness Among Those at Risk for Mental Illness: Results of a Randomized Controlled Trial - Nelson-Coffey, S. Katherine; Bohlmeijer, Ernst T.; Schotanus-Dijkstra, Marijke (Frontiers in Psychology, 2021)
People with reduced levels of mental well-being might be at risk for developing future mental illness. Although several positive psychology interventions successfully improve mental well-being and psychological distress, less is known about their efficacy in a sample at risk for mental disorders. A Dutch sample of 289 participants with low or moderate levels of well-being were randomly assigned to other-focused kindness with reflection, other-focused kindness without reflection, self-focused kindness, or waitlist control (Trial register: NTR6786). Results of multilevel growth curve analyses revealed that other-focused kindness, but not self-focused kindness, led to improvements in the primary outcome mental well-being relative to waitlist control up to 6-week follow-up. By contrast, only other-focused kindness without reflection led to improvements in psychological distress. The three kindness conditions mainly did not differ from one another, and mainly no differences were found up to 6-months follow-up. An exception was that perceived stress was significantly more reduced up to 6-week and 6-months follow-up when people practiced other-focused kindness without reflection then when participants had practiced self-focused kindness. These findings point to the benefits of practicing kindness for others when people might be at risk for future mental illness. The study also indicates that reflecting about practicing kindness does not seem to have added value.